2008
DOI: 10.1016/j.ajhg.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Apparently Balanced Chromosomal Rearrangements from the Developmental Genome Anatomy Project

Abstract: Apparently balanced chromosomal rearrangements in individuals with major congenital anomalies represent natural experiments of gene disruption and dysregulation. These individuals can be studied to identify novel genes critical in human development and to annotate further the function of known genes. Identification and characterization of these genes is the goal of the Developmental Genome Anatomy Project (DGAP). DGAP is a multidisciplinary effort that leverages the recent advances resulting from the Human Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
1
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 34 publications
3
87
1
16
Order By: Relevance
“…Three unbalanced translocations had breakpoints consistent with NAHR between pairs of LINEs, HERVs, or short SDs; however, most breakpoint junctions had blunt ends, microhomology, inserted sequence, or inversions, indicating that most unbalanced translocations arise by NHEJ or MMBIR. These breakpoint signatures are similar to those from sequenced balanced translocations [5153]. On the other hand, sequencing another cohort of nine unbalanced translocations revealed that six were mediated by NAHR between 6 kb LINE, 3 kb HERV, or 1.7 kb SD pairs that are each >90% identical [45].…”
Section: Simple Interchromosomal Svsupporting
confidence: 58%
See 1 more Smart Citation
“…Three unbalanced translocations had breakpoints consistent with NAHR between pairs of LINEs, HERVs, or short SDs; however, most breakpoint junctions had blunt ends, microhomology, inserted sequence, or inversions, indicating that most unbalanced translocations arise by NHEJ or MMBIR. These breakpoint signatures are similar to those from sequenced balanced translocations [5153]. On the other hand, sequencing another cohort of nine unbalanced translocations revealed that six were mediated by NAHR between 6 kb LINE, 3 kb HERV, or 1.7 kb SD pairs that are each >90% identical [45].…”
Section: Simple Interchromosomal Svsupporting
confidence: 58%
“…In both unbalanced translocation studies, LINE and HERV elements were capable of NAHR, whereas no Alu – Alu events were detected [45,46]. Indeed, Alu – Alu recombination has been reported in only three translocations [5355]. This trend suggests that, for NAHR-mediated rearrangements, those that are interchromosomal may require longer stretches of homology and greater sequence identity than those that are intrachromosomal.…”
Section: Simple Interchromosomal Svmentioning
confidence: 99%
“…All large-insert sequencing methods allowed generation of paired-end reads with median insert size of 2.5–3.5 kb as opposed to 300 bp using conventional methods. A subset of samples were prepared with standard short-insert paired-end protocols (n=12) or targeted sequencing of the breakpoints based on previous positional cloning to narrow the breakpoint regions (n=34), as previously described 7,11,81 . Of note, 87 BCAs had been initially reported in the literature, though many had not been mapped to sequence resolution (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Several techniques had been developed to map chromosome breakpoints to the kilobase level (Chen et al, 2008, Gribble et al, 2009, Higgins et al, 2008, Sobreira et al, 2011, Talkowski et al, 2011, Talkowski et al, 2012, Vergult et al, 2014). However, these techniques are time-consuming, expensive, and do not provide information about the breakpoint-linked SNPs for use in later PGDs.…”
Section: Introductionmentioning
confidence: 99%